Seaweed afforestation at large-scales exclusively for carbon sequestration: Critical assessment of risks, viability and the state of knowledge - Ross, Finnley; Tarbuck, Patrick; Macreadie, Peter I. (Frontiers in Marine Science, 2022)
There have been discussions of scaling up offshore seaweed cultivation and sinking it exclusively for carbon sequestration (‘ocean afforestation’) and thereby help mitigate climate change, but is this concept feasible? Here we investigate the feasibility of ocean afforestation across five perspectives: 1) Ecological feasibility; 2) Technical feasibility; 3) Economic feasibility; 4) Co-benefits and risks; and 5) Governance and social considerations. Optimising ecological factors such as species selection and use of currents, alongside the use of low-cost biodegradable rafts in theory could see this concept scaled globally. An area of 400,000km2 or 16.4 billion biodegradable rafts would be needed for 1 gigatonne of CO2 fixation given roughly 16 rafts of 25m2 each would be needed per tonne of CO2 fixation. However, CO2 fixation (calculated from net primary productivity) and carbon sequestration (carbon permanently removed from the atmosphere) are fundamentally different processes, yet this distinction is often overlooked. Quantifying carbon sequestration from ocean afforestation remains elusive given several outstanding oceanic biogeochemical considerations. For example, the displacement of phytoplankton communities and their associated carbon sequestration via nutrient reallocation is a critical knowledge gap in understanding the climate change mitigation potential of ocean afforestation. Ocean afforestation also carries complex risks to marine ecosystems, for example, the impact on benthic communities of seaweed deposition. Additionally, governance and social challenges exist such as the legality of operation in relation to ocean treaties. The concept of ocean afforestation is still in its infancy, and while there are large research gaps, further investment into research should be given before the concept can be adequately compared against the suite of potential ocean-based climate change mitigation strategies.